ASOSIASI FUNGI MIKORIZA ARBUSKULA (FMA) PADA RHIZOPHORA spp DI DESA TERUSAN KECAMATAN MEMPAWAH HILIR KALIMANTAN BARAT - Abdul Samad; Burhanuddin .; Iskandar AM (Universitas Tanjungpura, 2017)
Symbiosis of Arbuscular Mycorrhizal Fungi (AMF) with Rhizophora spp was observed a Terusan Village, Mempawah Hilir Districts, West Kalimantan.. Purpose of the study is : (1) want to obtain information of association of AMF with Rhizophora spp , (2) the types of AMF associated with Rhizophora spp. This research was conducted for 3 months in Terusan Village, Mempawah Hilir District, West Kalimantan and Silviculture Laboratory, Faculty of Forestry, Tanjungpura University. The research was conducted by lane technique survey method. The results of this study showed that there are 7 types of AMF namely Gigaspora sp, Glomus sp1, Glomus sp2, Glomus sp3, Glomus sp4, Glomus sp5, and Glomus sp6. The total number of spores there are 2,903 spores while for the root sample found the internal hyphae and vesicle in the root.Keywords: Rhizophora spp, mycorrhiza, Mangrove, Terusan Village